2013
DOI: 10.1179/1743281212y.0000000090
|View full text |Cite
|
Sign up to set email alerts
|

Model for diffusion coefficient estimation of calcium ions in CaO–Al2O3–SiO2slags

Abstract: As a common component in metallurgical slag, CaO plays an important role in desulphurisation, dephosphorisation and absorption of non-metallic inclusions. In order to better understand the mechanism of the slag/metal reactions, the diffusion dynamics of calcium ions in CaO-Al 2 O 3 -SiO 2 slags were studied. It was found that there was almost a linear relation between the logarithms of pre-exponential factor and diffusion activation energy. By combining the relation between the diffusion activation energy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Experimental research has found that the mass transfer in the slag is typically the ratedetermining step for the CaO dissolution in SiO 2 -CaO-Al 2 O 3 slag. A number of researchers have also deduced the diffusivity from dissolution rate data [3][4][5][6][7][8][9][10][11]. A short summary with the diffusion coefficients together with the respective slag composition and temperature is listed in Table 1.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental research has found that the mass transfer in the slag is typically the ratedetermining step for the CaO dissolution in SiO 2 -CaO-Al 2 O 3 slag. A number of researchers have also deduced the diffusivity from dissolution rate data [3][4][5][6][7][8][9][10][11]. A short summary with the diffusion coefficients together with the respective slag composition and temperature is listed in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Ren et al [11] developed a model for estimating the diffusion coefficient related to the structure of the slag instead of viscosity and electrical conductivity. The structure of the slag is often described by optical basicity, free oxygen, bridging oxygen, non-bridging oxygen and the ratio of non-bridging oxygen to tetrahedral cations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation